Recovering an Irish Voice from the American Frontier : The Prose Writings of Eoin Ua Cathail - Ua Cathail, Eoin, 1840-1928 (Book collections on Project MUSE., 2021)
"Eoin Ua Cathail, a native of Templeglantine, County Limerick, emigrated to the United States in 1863. Recovering an Irish Voice, translated and edited by Patrick J. Mahoney, is a bilingual compilation of Ua Cathail's stories based on his experiences in the West and Midwest. These stories have largely eluded scholarly attention to date, as they were written in the Irish language. The author draws on the popular American Dime Novel genre throughout to offer unique reflections on nineteenth-century American life. His writings are marked by the eccentricities and bloated claims characteristic of much American Western literature of the time, while also offering valuable transnational insights into Irish myth, history, and the Gaelic Revival movement. Ua Cathail's work can be divided into two distinct periods: The first deals with his time as a member of a government mule train accompanying the U.S. military during the Plains Indian Wars, while his later work recalls his time in the booming lumber trade of the Great Lakes region. He depicts fierce encounters with Native American tribes, while also subtly commenting on the hypocrisy of many famine-era Irish immigrants who failed to recognize the parallels between their own plight and that of dispossessed Native peoples. These views are further challenged by his stories set in the upper Midwest. While Ua Cathail is quick to praise infrastructural advances and the opportunities that the land presented to newly arrived immigrants, he is elsewhere remorseful of mass deforestation and damning of the greed of some business owners. This bilingual volume, with facing Irish-English pages, marks the first publication of Ua Cathail's work in both the original Irish and in translation. It also includes a foreword from historian Richard White, a comprehensive introduction by Mahoney, and a host of previously unpublished historical images"--